2022
DOI: 10.1186/s41182-022-00421-8
|View full text |Cite
|
Sign up to set email alerts
|

Snakebite victim profiles and treatment-seeking behaviors in two regions of Kenya: results from a health demographic surveillance system

Abstract: Introduction Snakebites are a major cause of permanent injury and death among poor, rural populations in developing countries, including those in East Africa. This research characterizes snakebite incidence, risk factors, and subsequent health-seeking behaviors in two regions of Kenya using a mixed methods approach. Methods As a part of regular activities of a health demographic surveillance system, household-level survey on snakebite incidence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Similar findings have been reported in Ghana, where HCWs overestimated their knowledge about snakebite management [ 24 ], and in Nigeria, where the knowledge about SAV among HCWs was grossly inadequate [ 28 ]. Patterns of lack of knowledge among HCWs on snakebite and SAV prescription and administration have also been reported in Brazil, Palestine, Kenya, Uganda, and Zambia [ 16 , 18 , 33 ]. While over two-thirds of the HCWs said that they had received training on snakebite management, this mainly was during their pre-service training at school, and it was unclear how the training was conducted.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar findings have been reported in Ghana, where HCWs overestimated their knowledge about snakebite management [ 24 ], and in Nigeria, where the knowledge about SAV among HCWs was grossly inadequate [ 28 ]. Patterns of lack of knowledge among HCWs on snakebite and SAV prescription and administration have also been reported in Brazil, Palestine, Kenya, Uganda, and Zambia [ 16 , 18 , 33 ]. While over two-thirds of the HCWs said that they had received training on snakebite management, this mainly was during their pre-service training at school, and it was unclear how the training was conducted.…”
Section: Discussionmentioning
confidence: 87%
“…In Malawi, a low-income country in southern Africa, there is a complete absence of literature on the estimated number of snakebites and treatment. A systematic review of 14 studies showed that most snakebite victims do not seek medical care at healthcare centers or hospitals due to distance to a health facility, financial constraints, and lack of availability of SAVs [ 16 18 ]. Studies done in rural Cameroon, Myanmar, Rwanda, and Ghana have also shown that traditional medicine is preferred and more trusted to cure snakebites than”western” bio-medicine [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The health economic impact of snakebite treatment estimates the cost of managing snakebite envenoming at the local hospital level since victims are responsible for the cost [30, 28]. Antivenoms are frequently inaccessible to both patients and the suffering healthcare system due to their high cost [31].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, patients may spend hours or even days before reaching a medical facility equipped to treat SBE. Such delays, especially in those patients with severe SBE, have been shown to increase the risk of a poor outcome [ 12 , 14 , 15 , 29 , 30 , 31 , 32 ].…”
Section: Delays To Treatmentmentioning
confidence: 99%